The railroads, the nation's first big business : - Chandler, Alfred Dupont (Harcourt, Brace & World, 1965)
In Six Parts: The Railroads as Promoters of Economic Change, The Beginning of Modern Corporate Finance, The First Modern Corporate Management, The Beginnings of Modern Labor Relations, New Ways of Competition, The Beginnings of Modern Governmental Regulation of Business